Knowledge and Behaviour about Adolescent Reproductive Health in Yogyakarta, Indonesia - Solikhah Solikhah; Sitti Nurdjannah (Intelektual Pustaka Media Utama, 2015)
Lack of knowledge about reproductive health in adolescent, making teens easily influenced by misinformation and harmful to their reproductive health. Health education plays an important role in increasing their knowledge and behavior of young people in order to maintain good reproductive health. The purpose of the research was to see the impact of health education on the knowledge and behavior of adolescents in reproductive health. Paired t test analysis results indicate that counseling on reproductive health effect on both knowledge about reproductive health (mean difference: 10.216, 95% CI: 6.622 to 13.809) and attitudes about reproductive health in adolescents (mean difference: 65.417, 95% CI: 11,176 to 61.690). Knowledge of adolescents about reproductive health would be beneficial in preparing the young people in good reproductive health issues so expect teenagers do not conflict with the norms prevailing in the community.